2013
DOI: 10.5588/pha.13.0005
|View full text |Cite
|
Sign up to set email alerts
|

Beyond drugs: tuberculosis patients in Bangladesh need nutritional support during convalescence

Abstract: high TB burden. 2,6,12 The effective management of TB therefore requires a detailed evaluation of nutritional status, as this can help to prevent or modify many complications of the disease.Signifi cant improvement has been achieved in TB control in Bangladesh in the last few years. 13 The government of Bangladesh, in partnership with different non-government organisations, including BRAC, has been implementing a community-based National Tuberculosis Control Programme (NTP) based on the DOTS strategy since 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The discussion of nutritional status before, during and after tuberculosis treatment in patients treated in Brazil is particularly intriguing, as the brazilian health care system provides free access to tuberculosis and HIV treatments. This is a unique situation, and it is not expected that findings from studies conducted in other countries [ 3 , 4 , 11 , 18 , 19 ] could be extrapolated to brazilian patients.…”
Section: Introductionmentioning
confidence: 98%
“…The discussion of nutritional status before, during and after tuberculosis treatment in patients treated in Brazil is particularly intriguing, as the brazilian health care system provides free access to tuberculosis and HIV treatments. This is a unique situation, and it is not expected that findings from studies conducted in other countries [ 3 , 4 , 11 , 18 , 19 ] could be extrapolated to brazilian patients.…”
Section: Introductionmentioning
confidence: 98%
“…Our data indicate that more men compared to women were older and had a lower BMI than the women. Older age at presentation, more co-morbidity, limited access to health services and poor adherence are associated with mortality among older men [ 17 , 18 , 22 25 ]. Findings from this study are consistent with previous research which showed that patients with a higher BMI had a lower risk of death [ 23 , 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not surprising because low BMI means inadequate dietary intake, which is a common occurrence in impoverished communities, WHO lack employment, hence lack a means to buy food [8]. Poverty is a product of lack of employment which is associated with poor nutrition status and has a dose response relationship with incidence of TB disease [12,13]. The role of diet in patients with TB disease has been studied for decades [14].…”
Section: Discussionmentioning
confidence: 99%
“…The role of diet in patients with TB disease has been studied for decades [14]. Poor nutrition has been found to be a strong risk factor for TB reactivation and mortality; food supplementation has been shown to accelerate therapeutic benefits [13]. A HIV infected cohort in Tanzania, showed that low BMI or falling BMI is associated with a higher risk of developing HIV associated TB [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation